2015
DOI: 10.5830/cvja-2014-064
|View full text |Cite
|
Sign up to set email alerts
|

Redo off-pump coronary artery bypass grafting via a left thoracotomy : cardiovascular topic

Abstract: SummaryBackgroundIn this study, we retrospectively reviewed our experience in a meticulously selected group of patients undergoing redo off-pump coronary artery bypass graft (CABG) surgery from the descending aorta to the circumflex artery (Cx) and its branches.MethodsBetween January 2001 and October 2013, 32 patients at our hospital underwent redo off-pump CABG from the descending aorta to the Cx and its branches via a left posterolateral thoracotomy. Of these patients, 27 were male (84.3%) and five were fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…One other study reported a prevalence of 25.4% (95%CI: 16.3–37.3) in 63 patients with systemic lupus erythematous in Kenya [ 29 ]. In one study conducted in Mauritius, the prevalence of PH was 68.7% (95%CI: 62.8–74.1) among 259 patients with cardiac surgery [ 42 ]. One study reported a prevalence of 7.4% (95%CI: 4.6–11.9) in 202 patients with systemic sclerosis in Algeria [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…One other study reported a prevalence of 25.4% (95%CI: 16.3–37.3) in 63 patients with systemic lupus erythematous in Kenya [ 29 ]. In one study conducted in Mauritius, the prevalence of PH was 68.7% (95%CI: 62.8–74.1) among 259 patients with cardiac surgery [ 42 ]. One study reported a prevalence of 7.4% (95%CI: 4.6–11.9) in 202 patients with systemic sclerosis in Algeria [ 39 ].…”
Section: Resultsmentioning
confidence: 99%